Growth and Persistence of Snakehead Fry Treated with Feed from Snail Flour - Ade Dwi Sasanti; Yulisman Yulisman (Research Center for Suboptimal Lands (PUR-PLSO), Universitas Sriwijaya, 2012)
Sasanti & Yulisman. 2012. Growth and Persistence of Snakehead Fry TreatedÂ with Feed from Snail Flour. JLSO 1(2):158-162. An experiment was conducted to observe the effects of feed from snail flour on the growth and survival rate of snakehead fish (Channa striata)fry. There were three treatments, each had three replications, stocked with 20 fry. The three diets treatments were artificial feed A with 35% snail flour, artificial feed B with 40% snail flour and artificial feed C with 45% snail flour. Snail flour was made from Pomacea sp. Survival and growth rate of fry were not significantly different among the three different treatments.